Study Comparison of Learning Outcomes between the User and Non User LEKER GABEL with Hotpotatos in Islamic University Of Jember - Fury Styo Siskawati (Jurnal Axioma : Jurnal Matematika dan Pembelajaran, 2017)
The purpose of this research is to know the difference of mathematics student learning outcomes users and non users LEKER GABEL with Hotpotatos at Universitas Islam Jember. Then to know the results of better learning mathematics between users and non users LEKER GABEL with Hotpotatos on the Structure of Algebra at Universitas Islam Jember. The kind of this research is comparative research with quantitative approach. The data collecting methods used is documentation, questionnaires and tests. The results of the research is the value of t-test is 1.854 and t table is 1.684 it appears that at the level of significance of 5% t-test> t table so that Ha accepted and Ho rejected. The conclusion that can be drawn from the results is there are differences in learning outcomes of students' mathematics students users and non users LEKER GABEL with Hotpotatos on the Structure of Algebra at Universitas Islam Jember. Then also the results the student learning of LEKER GABEL users with Hotpotatos better than student learning outcomes is not a user LEKER GABEL with Hotpotatos on the Structure of Algebra at the Universitas Islam Jember.Keywords: mathematics learning outcomes, LEKER GABEL and Hotpotatos